Management of cracked tooth using simvastatin as intracanal medicament - Mohamed Fawzy (10724622) (2020)
Cracked tooth syndrome is presented as pain associated with biting and sensitivity. Intracanal medication with simvastatin stimulates hard tissue formation at crack line, and the tooth was functioning on the follow-ups. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.3315